Design and test of a custom instrumented leg press for injury and recovery intervention - James, D. A.; Simjanovic, M.; Leadbetter, R.; Wearing, S. (Procedia Engineering, 2014)
There is an increasing desire and emphasis to integrate assessment tools into the everyday training environment of athletes. These tools are intended to fine-tune athlete development, enhance performance and aid in the development of individualised programmes for athletes. The areas of workload monitoring, skill development and injury assessment are expected to benefit from such tools. This paper describes the development of an instrumented leg press and its application to testing leg dominance with a cohort of athletes. The developed instrumented leg press is a 45° reclining sled-type leg press with dual force plates, a displacement sensor and a CCD camera. A custom software client was developed using C#. The software client enabled near-real-time display of forces beneath each limb together with displacement of the quad track roller system and video feedback of the exercise. In recording mode, the collection of athlete particulars is prompted at the start of the exercise, and pre-set thresholds are used subsequently to separate the data into epochs from each exercise repetition. The leg press was evaluated in a controlled study of a cohort of physically active adults who performed a series of leg press exercises. The leg press exercises were undertaken at a set cadence with nominal applied loads of 50%, 100% and 150% of body weight without feedback. A significant asymmetry in loading of the limbs was observed in healthy adults during both the eccentric and concentric phases of the leg press exercise (P < .05). Mean forces were significantly higher beneath the non-dominant limb (4-10%) and during the concentric phase of the muscle action (5%). Given that symmetrical loading is often emphasized during strength training and remains a common goal in sports rehabilitation, these findings highlight the clinical potential for this instrumented leg press system to monitor symmetry in lower-limb loading during progressive strength training and sports rehabilitation protocols.